Displacements and philosophy: a study on movement and space perceptions involving children - Barreiros, Carolina Miguel dos Santos; Humberto, Mateus; Berle, Simone (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This study addresses children's perceptions on space and movement, on the basis of an experience of philosophical dialogue at a kindergarten in Lisbon, Portugal. According to the narration of the experience lived by adults and children, we aim to reflect upon how dialogue relations are established in the context of academic research. This experience involved the exact and human sciences, which are expressed in pedagogy, architecture and transports. The meetings were intended to spark discussions based on issues related to mobility and remaining in public spaces such as school commutes, playground games, and outdoor trips. As the meetings ended, family members were asked to reply to a questionnaire aimed at assessing the relevance of philosophical practices with children on the basis of the perception on mobility practices and remaining in public spaces. By observing the development of this matter at each meeting and family members' responses, it was possible to study the influence of school environments and some family experiences on habit formation from an early age. These habits serve as the basis for educational practices aimed at strengthening autonomy and welfare in shared public spaces.